Reliability of the French-Canadian adaptation of the Personality Assessment Inventory: Medical–legal implications. Issue 1 (2nd January 2021) - Jeffay, Eliyas; Sekely, Angela; Lacerte, Michel; Zakzanis, Konstantine K.
Abstract : The Personality Assessment Inventory (PAI) is a reliable multidimensional psychometric inventory that is increasingly being used in the medical–legal context. To date, 18 language adaptations of the PAI exist, yet only the Spanish, Greek and German language versions have been examined psychometrically. This study evaluated the psychometric properties of the French-Canadian version of the PAI by comparing mean scale and subscale scores between the French-Canadian and English language versions, and analyzing the internal consistency and mean item inter-correlations (MICs) of each version in a sample of 50 bilingual university students. Cronbach's alphas ranged from −.57 to .80 in the French-Canadian version and from −1.10 to .83 in the English version, with most scales being below .70, indicating inadequate internal consistency. In addition, most of the MICs were below .20, indicating a lack of item homogeneity. Caution is given to this adaptation of the PAI in the medical–legal context.